2015
DOI: 10.11622/smedj.2015033
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant analysis for predictor of falls in stroke patients by using the Berg Balance Scale

Abstract: INTRODUCTIONAn observational study was carried out to estimate the strength of the relationships among balance, mobility and falls in hemiplegic stroke inpatients. The objective was to examine factors that may aid in the prediction of the likelihood of falls in stroke patients.METHODS A total of 53 stroke patients (30 male, 23 female) aged 67.0 ± 11.1 years were interviewed regarding their fall history. Physical performance was assessed using the Berg Balance Scale (BBS) and the Functional Independence Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 22 publications
0
22
0
10
Order By: Relevance
“…Previously numerous cut-off points have been reported for the BBS. A cut-off score of lesser than 31 on the BBS is an indication of fall risk in stroke, 29 and less than 19 indicates stroke survivors with low function. 15 We are the first to report cut-off points for the BBS and Mini-BESTest to identify fast walkers.…”
Section: Discussionmentioning
confidence: 99%
“…Previously numerous cut-off points have been reported for the BBS. A cut-off score of lesser than 31 on the BBS is an indication of fall risk in stroke, 29 and less than 19 indicates stroke survivors with low function. 15 We are the first to report cut-off points for the BBS and Mini-BESTest to identify fast walkers.…”
Section: Discussionmentioning
confidence: 99%
“…[21] A variety of cutscores are available in the literature, allowing clinicians to identify “at-risk” clients. Fall risk cutscores range from 31 [24] to 50 [25] for discriminating between fallers and non-fallers, and 42 [26] to 52 [11] for identification of “multiple fallers” or “injurious falls” among individuals with stroke. Given the balance requirements for maintaining stability, the relationship between BBS scores and fall risk is not surprising; however, BBS scores also appear to provide insight into walking ability in individuals with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that patients who had a history of falling during hospitalization were more likely to fall after discharge [2,3]. Attributes of physical function, such as balance [2–4] and lower extremity strength [5], have also been shown to predict falls among stroke survivors. Other factors, such as taking more medications [2], impaired cognition [6], and depression [5], have also been identified as potential risk factors.…”
Section: Introductionmentioning
confidence: 99%